The Prognosis Role of AST/ALT (De Ritis) Ratio in Patients with Adult Secondary Hemophagocytic Lymphohistiocytosis - Guangli Yin; Changfeng Man; Shengen Liao; Hongxia Qiu (Hindawi Limited, 2020)
Purpose. Secondary hemophagocytic lymphohistiocytosis (sHLH) accompanied by liver involvement, characterized by hepatomegaly and increased liver enzymes, is usually associated with elevated mortality. However, the magnitude of these associations remains unknown. Our objective was to assess the associations of the aspartate transaminase/alanine transaminase (AST/ALT, De Ritis) ratio with overall survival among adult patients with sHLH. Methods. A retrospective analysis was performed on 289 patients aged 18-86 years with complete serum transaminase data at diagnosis of sHLH. Multivariate Cox regression analyses and restricted cubic splines were conducted to address the association between the De Ritis ratio and the risk of mortality. Results. The median De Ritis ratio for the entire study population was 1.34 (IQR: 0.84-2.29). After a median follow-up time of 60 (range 17-227.5) days, 205 deaths occurred. After fully adjusting for hepatomegaly, albumin, fibrinogen, EBV, ferritin, etiologies, and treatment strategies, the adjusted hazard ratios (HRs) with corresponding confidence intervals (CIs) of mortality for the 2 st tertile and 3 st tertile were 1.2 (0.8-1.7) and 1.6 (1.1-2.2), respectively (P<0.01 for trends). Restricted cubic spline confirmed a linear association between the log2-transformed De Ritis ratio and the risk of mortality. Moreover, this trend persisted in subgroups with MHLH, hyperferrinaemia, sCD25≤20,000 ng/L, patients without EBV infection, and those received treatment. Conclusions. The De Ritis ratio is a strong and independent predictor for overall survival in patients with sHLH. As a readily available biomarker in routine clinical practice, it is used to identify patients with sHLH with inferior overall survival.